ANALYTICAL PSYCHOLOGY AND SPORT epistemology, theory and practice. - Cowen, Andrew ([S.l.] : ROUTLEDGE, 2024)
Analytical Psychology and Sport: Epistemology, Theory and Practice introduces the epistemology and psychology of C.G. Jung to the sport psychology readership. In doing so, it considers for the first time the implications of analytical psychology with respect to theorising on well-established psychological phenomena in sport, including confidence, mental toughness and psychological momentum. To date, sport psychology has given limited consideration to how epistemology itself informs the development of knowledge. In light of Jung's epistemological contributions and more recent developments in psychology, this new book explores how a renewed focus on the philosophy of science can help facilitate the development of sport psychology as a scientific discipline. This new research volume investigates analytical psychology in relation to a number of novel topics, including person-athlete interdependence and the psychology of performance variation, and will be key reading for academics and students of sport and exercise psychology, analytical psychology and related disciplines.
Keywords: Sports -- Psychological aspects; SPORTS & RECREATION / Coaching / General; SPORTS & RECREATION / General